READINESS OF CENTRAL HALMAHERA REGENCY IN CREATING SMART TOURISM FOR SUSTAINABLE CITY AND ECONOMIC DEVELOPMENT - Christienti Tuny (Sean Institute, 2023)
The purpose of this study is to describe the readiness of Central Halmahera Regency in realizing smart tourism in every sustainable urban and economic development. The research method used is literature review and data obtained from journal sources, books and the official website of the manager, as well as personal experience and observations. The results of the study show that the role and attention of the government and local management institutions is still not optimal, as can be seen from the existing systems in several tourist destinations where the system is still chaotic and unclear, even though there are still many that are not in accordance with the tourism component. As for the city itself, Central Halmahera Regency still needs improvement in its readiness to become a smart city because it still needs a lot of education and experience, both from the community and the government. Tourism potential, awareness and increasing knowledge about Smart City development need to be increased so that the implementation of Smart City can be realized in Central Halmahera Regency and making Central Halmahera Regency one of the cities that has the best tourism